2011
DOI: 10.1002/jsfa.4334
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between high hydrostatic pressure extraction and heat extraction of ginsenosides from ginseng (Panax ginseng CA Meyer)

Abstract: HHPE used for red ginseng processing contributes to enhanced extraction efficiencies of functional materials such as ginsenosides through cell structure modification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 30 publications
(29 reference statements)
0
45
0
Order By: Relevance
“…Specifically, the amounts of ginsenosides Rb 2 and Rd in the HRG were highest among the ginseng extracts. Lee et al (8) compared ginsenosides compositions between red ginseng under high hydrostatic pressure extraction (HHPE) and red ginseng under heat extraction (HE). Total ginsenoside and ginsenosides Rg 1 , Rg 2 +Rh 1 , Rb 1 , Rb 2 , Rd, and F2 were increased under HHPE compared to HE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the amounts of ginsenosides Rb 2 and Rd in the HRG were highest among the ginseng extracts. Lee et al (8) compared ginsenosides compositions between red ginseng under high hydrostatic pressure extraction (HHPE) and red ginseng under heat extraction (HE). Total ginsenoside and ginsenosides Rg 1 , Rg 2 +Rh 1 , Rb 1 , Rb 2 , Rd, and F2 were increased under HHPE compared to HE.…”
Section: Discussionmentioning
confidence: 99%
“…Usage of low temperature (between −20 and 60 o C) in the HHP process results in an increase of extraction efficiency without destroying heat-sensitive bioactive constituents (7). Lee et al (8) reported that the amount of major ginsenosides found in high hydrostatic pressure extracts of Korea ginseng was 45% more compared to the extracts using conventional methods.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for higher extraction of Rg1 and Rb1 in the three-enzyme combination CAP could be due to the enhanced activity of cellulase and amylase at HHP as reported earlier. Additionally, HHP was reported to disrupt ginseng cells and release the starch materials;[3233] hence treatment with cellulase and amylase hydrolyze the cellulose in the cell wall and starch released from the cells, respectively, to facilitate higher release of ginsenosides. We observed, in our previous study, that treatment with cellulase converts ginsenoside Rb1 to Rd.…”
Section: Discussionmentioning
confidence: 99%
“…The technique not only took a shorter time but also afforded higher extraction yields of ginsenosides (Yutang et al 2008 ). High-pressure extraction of fresh and red ginseng was found to be more effective than thermal extraction (Lee et al 2011 ).…”
Section: Herbs and Rootsmentioning
confidence: 99%